OC-042 Benefits of Service Redesign with a Tertiary Symptomatic Colorectal EMR Service Managed within Bowel Cancer Screening Service Model. (17th August 2016) - Keeley, G; Gibson, HL; O'Toole, P; Mbuyongha, M; Fitzgerald, G; Gould, D; Sarkar, S
Abstract : Introduction: One of the high quality service developments in endoscopy in the UK has been the introduction of the Bowel Cancer Screening Programme due to the rigorous quality assurance not just of the colonoscopy but of all aspects of the patient journey. Whilst the Royal Liverpool is a tertiary referral site for colorectal complex polyp/Endoscopic Mucosal Resection for BCSP and the symptomatic service for the North-West, the patient journey and quality of service varied significantly depending whether they were referred through via the BCSP or the symptomatic route. Methods: We modelled the patient pathway within the symptomatic service to the BCSP standard of care. We seconded two SSPs and BCSP admin to work 50% with the EMR service and 50% within BCSP. All referrals were initially reviewed by EMR specialist endoscopists and then handed to the SSPs to be entered onto a bespoke database. Telephone assessment of patients was performed by an SSP who actively managed the patients co-morbidities and charted them on the database. Patients were listed onto dedicated EMR lists with adequate slot allocations as determined by the EMR endoscopist. Post procedure, patients had a follow-up phone call and their histology and post discharge follow up was monitored and managed by the team including MDT handover in the referral centres. Results: Since the start of the service (24 th August 2015) 138 patients have been managed through the service. The mean age was 77 years. Referral pathways have included:51% external tertiary referrals, 6% from MDT and 43% internal tertiary referrals. 31 telephone assessments have been performed. In 25% patients a successful intervention by the team resulted in a positive outcome. These included interventions in; Pre-procedure work up & management of co-morbidities (n = 14), administration (n = 12), post-procedure complications (n = 5) and change in management following histology results (n = 3). See Table for full details Conclusion: Re-design of the symptomatic EMR service using the expertise within our BCSP with similar principles in pathway management has had a significant impact on patient safety and outcomes within this service. Disclosure of Interest: None Declared